Gay-Straight Alliances, School Functioning, and Mental Health: Associations for Students of Color and LGBTQ Students. Issue 2 (March 2021) - Baams, Laura; Russell, Stephen T.
Utilizing a school-based sample of 895, 218 students aged 10–18 years old, we examine differences in students' school functioning, substance use, and mental health in schools with and without Gay-Straight Alliances (GSAs). In addition, we examine whether GSA presence is associated with these outcomes for students of color and LGBTQ students. Overall, students in schools with GSAs were found to report better school functioning, lower substance use, and better mental health. For students of color, the association between the presence of a GSA and mental health and substance use was not as strong as it was for non-Hispanic white students. Further, for LGBTQ students, the association between the presence of a GSA and school functioning was not as strong as it was for non-LGBTQ students. Future research is necessary to ascertain the function of GSAs, especially for marginalized youth.